SOLUSI STRATEGIS PENGENTASAN KEMISKINAN DI KABUPATEN PANDEGLANG PROVINSI BANTEN - Ipah Ema Jumiati; Ayuning Budiati; Riny Handayani; Rahmawati - (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2019)
It is not easy to build understanding of poverty because it involves various dimensions. Understanding poverty is very diverse, ranging from the inability to meet basic consumption needs and improve conditions to a broader understanding that includes social and moral components. According to Presidential Regulation of the Republic of Indonesia Number 131 Year 2015 concerning Determination of Underdeveloped Regions in 2015 - 2019. Pandeglang Regency and Lebak Regency are included in the category of disadvantaged areas. Pandeglang Regency has a poverty rate of 9.74 percent, followed by Lebak Regency 8.64 percent, Tangerang Regency 5.39 percent, Serang Regency 4.63 percent, Tangerang City 4.95 percent, Cilegon City 3.52 percent, Serang City 5, 57 percent, and South Tangerang City 1.76 percent. For the Solidarity Line in Pandeglang District the latest data is in the range of 267,752 rupiah / capita / month, the sixth lowest after Lebak Regency (246,389) and Serang Regency (256,660). This research was conducted to analyze the causal factors and explore the potential for poverty alleviation in Pandeglang Regency, Banten Province. In this study using quantitative methods and supported by qualitative. Quantitative methods have the advantage of validating natural science: explicit, standardized procedures; precise numerical measurement; and replication. (Neuman, 2006). While the qualitative approach used as a support is a process of research and understanding based on a methodology that investigates a social phenomenon and human problems in which this approach, the researcher makes a complex picture, examines words, detailed reports from the viewpoint of respondents and conducts studies on situations which is natural (Creswell 1998). Research Results Show that the regional gap index represented by the Gini Ratio in Pandeglang District obtained an average Gini Ratio of 0.20 which can be categorized as Low Inequality, below the 2017 Province Gini Ratio in Banten which is 0.380 and the National Gini Ratio of 0.320. With Low Inequality indicates that most households have income that does not differ greatly from one another. However, other data obtained from observations and data collection in the field, critical area 1 is much lower Gini Rationya (0.15) compared to critical area 3 represented by Karangtanjung District (0.32). This means that in Sobang District the income gap between communities is relatively lower than in Karangtanjung District. Furthermore, a concerted effort is needed so that the gap does not get worse so that it triggers social jealousy among the community. The factors causing poverty gap in Pandeglang Regency, Banten Province are: a) Low Level of Education; b) Community life patterns; c) Skill limitations; d) Low population mobility; e) Number of family dependents. Keywords: Potential, Poverty Alleviation.